Research on Control Strategy of Transmission Testing Device for Electric Locomotive’s Auxiliary Converter System - HUANG Hai (机车电传动)
A new transmission testing device for electric locomotive’s auxiliary converter system was introduced, and structure of electric locomotive’s auxiliary convertor system and its working processes were illustrated. PWM rectifier was used as load unit to regulate inverter output current for implementing various test conditions, current control of which was based on AC voltage orientation theory to realize decoupling control, and voltage-forecasting method was used to improve control system performance.